Crystal engineering of a 1:1 5-fluorocytosine–4-hydroxybenzaldehyde cocrystal: insights from X-ray crystallography and Hirshfeld analysis - Marimuthu Sangavi; Marimuthu Mohana; Ray J. Butcher; Colin D. McMillen (Acta Crystallographica Section E: Crystallographic Communications)
The 1:1 cocrystal of 5-fluorocytosine (5FC) and 4-hydroxybenzaldehyde (4HB), C4H4FN3O·C7H6O2 has been synthesized and its structure characterized by single-crystal X-ray diffraction and Hirshfeld surface analysis. The compound crystallizes in the monoclinic P21/c space group. A robust supramolecular architecture is stabilized by N—H...O, N—H...N, C—H...O and C—H...F hydrogen bonds, forming R22(8), R44(22), R66(32), and R88(34) ring motifs. The N—H...O and N—H...N hydrogen bonds form strong directional interactions, contributing to the R22(8) and R88(34) motifs through dimeric and extended ring structures. O—H...O interactions link 5FC and 4HB molecules, generating an R66(32) ring that enhances the packing. Weaker C—H...F bonds help form the R44(22) tetrameric motif, supporting the overall three-dimensional supramolecular framework. Additionally, C—F...π interactions between the fluorine atom and the aromatic ring add further to the crystal cohesion. Hirshfeld surface analysis and two-dimensional fingerprint plots confirm that O...H/H...O contacts are the most significant, highlighting the central role of hydrogen bonding in the stability and organization of the crystal structure.